PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI TOP 100 TIBAN - Andi Kahar Hariadi (Journal of Social Sustainability Management, 2022)
This study aims to determine the effect of marketing mix and service quality on buying decision at TOP 100 Tiban. The design of this research is a type of quantitative research using a causal associative approach. The results based on the t test for marketing mix (product, price, place and promotion) have a value of 2,939; 4,454;4,378; and 5,801 all values of the four variables > 1,98525 and a significance of 0.000 < 0.05 which means that marketing mix has an effects on buying decision, while the t test value for service quality has a value of13,915 > 1,98525 and a significant 0.000 < 0.05 which means that sevice quality has an effect on buying decision. The F test results obtained a value of 48,829 > 2,31 with a significance value of 0.000 < 0.05, it can be concluded that marketing mix and service quality together have a positive and significant effect on buying decision.